A new muscle glycogen storage disease associated with glycogenin‐1 deficiency. Issue 6 (31st October 2014) - Malfatti, Edoardo; Nilsson, Johanna; Hedberg‐Oldfors, Carola; Hernandez‐Lain, Aurelio; Michel, Fabrice; Dominguez‐Gonzalez, Cristina; Viennet, Gabriel; Akman, H. Orhan; Kornblum, Cornelia; Van den Bergh, Peter; Romero, Norma B.; Engel, Andrew G.; et al.
<x xml:space="preserve">Abstract</x> We describe a slowly progressive myopathy in 7 unrelated adult patients with storage of polyglucosan in muscle fibers. Genetic investigation revealed homozygous or compound heterozygous deleterious variants in the glycogenin‐1 gene (GYG1). Most patients showed depletion of glycogenin‐1 in skeletal muscle, whereas 1 showed presence of glycogenin‐1 lacking the C‐terminal that normally binds glycogen synthase. Our results indicate that either depletion of glycogenin‐1 or impaired interaction with glycogen synthase underlies this new form of glycogen storage disease that differs from a previously reported patient with GYG1 mutations who showed profound glycogen depletion in skeletal muscle and accumulation of glycogenin‐1. Ann Neurol 2014;76:891–898